Internal neurolysis: 'nerve combing' for trigeminal neuralgia without neurovascular conflict – early UK outcomes. (4th March 2022) - Durnford, Andrew J.; Gaastra, Ben; Akarca, Danyal; Lodge, Amanda; Ewbank, Frederick G.; Noorani, Imran; Vajramani, Girish; Sparrow, Owen C.
Abstract: Introduction: Internal neurolysis (INL) is a surgical procedure where trigeminal nerve fibres are separated between the pons and porus trigeminus to relieve trigeminal neuralgia (TN). We report pain and functional outcomes to evaluate its safety and efficacy. Materials and methods: Prospective cohort of all patients undergoing retrosigmoid craniotomy and INL between 2015 and 2017 at University Hospital Southampton. Patients with type I (6) or type II (2) refractory TN and no clear neurovascular conflict were offered INL as an alternative to partial sensory rhizotomy. Barrow Pain Intensity Scale (BNI) and Brief Pain Inventory Facial scores (BPI-Facial) were assessed. Minimum follow-up was 2 years'. Results: Eight patients (7F:1M) underwent INL. Two had MS. Pre-operatively, all had severe pain (BNI grade V) and the median BPI-Facial score was 115 (range 79–123).. There were no unexpected complications. On last follow-up, six (75%) had no pain (BNI grade I), while two (25%) had recurred (at 5 and 27 months). Median BPI-Facial score for all patients on the last follow-up was 20 (range 18–91) reflecting dramatically improved quality of life and activities. Conclusions: INL is a potentially safe and effective treatment for refractory TN. Long-term efficacy is unknown, but early results are promising.